Transparency of Health Informatics Processes as the Condition of Healthcare Professionals’ and Patients’ Trust and Adoption: the Rise of Ethical Requirements - Séroussi, Brigitte; Hollis, Kate Fultz; Soualmia, Lina F. (Yearbook of Medical Informatics, 2020)
Objectives: To provide an introduction to the 2020 International Medical Informatics Association (IMIA) Yearbook by the editors.Methods: This editorial provides an introduction and overview to the 2020 IMIA Yearbook which special topic is: “Ethics in Health Informatics”. The keynote paper, the survey paper of the Special Topic section, and the paper about Donald Lindberg’s ethical scientific openness in the History of Medical Informatics chapter of the Yearbook are discussed. Changes in the Yearbook Editorial Committee are also described.Results: Inspired by medical ethics, ethics in health informatics progresses with the advances in biomedical informatics. With the wide use of EHRs, the enlargement of the care team perimeter, the need for data sharing for care continuity, the reuse of data for the sake of research, and the implementation of AI-powered decision support tools, new ethics requirements are necessary to address issues such as threats on privacy, confidentiality breaches, poor security practices, lack of patient information, tension on data sharing and reuse policies, need for more transparency on apps effectiveness, biased algorithms with discriminatory outcomes, guarantee on trustworthy AI, concerns on the re-identification of de-identified data.Conclusions: Despite privacy rules rooted in the Health Insurance Portability and Accountability Act of 1996 (HIPAA) in the USA and even more restrictive new regulations such as the EU General Data Protection Regulation published in May 2018, some people do not believe their data will be kept confidential and may not share sensitive information with a provider, which may also induce unethical situations. Transparency on healthcare data processes is a condition of healthcare professionals’ and patients’ trust and their adoption of digital tools.
Keywords: Informatics, medical; Health Information Technology; IMIA Yearbook of Medical Informatics; Artificial intelligence; Data sharing; Ethics